Enhancing Pregnancy Outcomes in Cattle: Effect of Hyaluronan-Enriched Embryo Transfer Medium on In Vitro Produced Embryos - N Saripadiya, Bhautik; K Hadiya, Kamlesh; S Layek, Siddhartha; P Patil, Sanket; Doultani, Shilpa; B Raval, Kathan; Raj, Sudharson; Karuppanasamy, Kuppusamy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Suboptimal pregnancy rates following the transfer of in vitro produced (IVP) bovine embryos remain a significant constraint in livestock genetic improvement programs. This study evaluated whether supplementing embryo transfer media with hyaluronan (HA), a key biomolecule in implantation, could improve pregnancy outcomes. Bovine IVP embryos were allocated to four treatment groups for transfer: two commercial media (ET-HEPES; IMV holding) and two in-house prepared media (with 0.5% HA; without HA). Key outcomes measured were in vitro hatching rate after a 24 h of incubation simulating transport, early embryonic death (EED) rate, and pregnancy rate at day 60 post-transfer in 120 recipient cattle (n=30 per group). The in-house medium with 0.5% HA yielded the highest pregnancy rate (20.0%), which was numerically superior to ET-HEPES (16.67%), IMV holding media (13.33%), and the non-supplemented in-house medium (3.33%). Furthermore, the non-supplemented medium resulted in a markedly higher EED rate (83.33%) compared to the HA-supplemented (33.33%) and commercial media groups. It is concluded that supplementing in-house embryo transfer media with 0.5% hyaluronan enhances pregnancy outcomes and represents a cost-effective and biologically superior alternative to standard commercial media for bovine embryo transfer programs.
Keywords: Bovine; Embryo Transfer; Hyaluronan; In Vitro Embryo Production; Pregnancy Rate